Produção de bioetanol a partir da fermentação de caldo de sorgo sacarino e cana-de-açúcar - Masson, Igor dos Santos [UNESP]; Costa, Gustavo Henrique Gravatim [UNESP]; Roviero, Juliana Pelegrini [UNESP]; Freita, Lidyane Aline de [UNESP]; Mutton, Miguel Angelo [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (Universidade Federal de Santa Maria, 2015)
Biofuels have great importance to supply the global energy demand. These fuels are produced from plant biomass, emit less carbon dioxide and particulate pollutants to the environment when used and have great advantage of being renewable fuels. Among the raw materials with potential for ethanol production, is cited sweet sorghum. This study aimed to compare industrial processing of genotype sorghum CVSW80007 and the cultivar sugar cane 'RB966928' for bioethanol production in early season. The analyzes performed were: brix, pH, ART, AR, total acidity, ARRT, glycerol, alcohol content, cell viability, shoots viability and buds. Regarding the chemical-technological characteristics, raw materials were suitable for industrial processing, with higher rates for sugar cane. The development of fermentations occurred appropriately for both, and the fermented must (wine) produced from the must of sugar cane had higher alcohol content and fermentation yield.

Os biocombustíveis apresentam-se com grande importância para suprir a demanda global de energia. São produzidos a partir de biomassa vegetal, emitem menor quantidade de dióxido de carbono e de partículas poluentes ao ambiente quando utilizados e possuem grande vantagem por serem combustíveis renováveis. Entre as matérias-primas com potencial para produção de etanol, cita-se o sorgo sacarino. Objetivou-se comparar o processamento industrial do genótipo de sorgo sacarino CVSW80007 e da cultivar de cana-de-açúcar 'RB966928' para produção de bioetanol em início de safra. As análises realizadas foram: brix; pH, ART, AR, acidez total, ARRT, glicerol, teor alcoolico, viabilidade celular, viabilidade de brotos e brotamentos. Quanto às características químico-tecnológicas, as matérias-primas apresentaram-se aptas ao processamento industrial, com índices superiores para a cana-de-açúcar. O desenvolvimento das fermentações ocorreu de forma adequada para ambas, sendo que o mosto fermentado (vinho), produzido a partir do mosto de cana-de-açúcar, apresentou maior teor alcoolico e rendimento fermentativo.
Bioethanol production from sweet sorghum broth and sugar cane fermentation
Keywords: Raw material; Sorghum bicolor (L.) Moench; Saccharum spp.; Yeast; Biomass; Matéria-prima; Sorghum bicolor (L.) Moench; Saccharum spp; Leveduras; Biomassa vegetal.